2011
DOI: 10.1101/gad.16997911
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific function of the noncoding Tsix RNA for Xist repression and Xi reactivation in mice

Abstract: The noncoding Tsix RNA is an antisense repressor of Xist and regulates X inactivation in mice. Tsix is essential for preventing the inactivation of the maternally inherited X chromosome in extraembryonic lineages where imprinted X-chromosome inactivation (XCI) occurs. Here we establish an inducible Tsix expression system for investigating Tsix function in development. We show that Tsix has a clear functional window in extraembryonic development. Within this window, Tsix can repress Xist, which is accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 48 publications
2
48
0
Order By: Relevance
“…The loss of Tsix antisense transcription through the Xist promoter has been shown to result in promoter-associated chromatin changes, allowing aberrant initiation of Xist transcription (9,10,40). In addition, forced Tsix expression during development results in Xist promoter methylation (41). Xist promoter methylation is also required to stably repress Xist at later stages of development in the absence of ongoing Tsix transcription, which is shut down in differentiated cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of Tsix antisense transcription through the Xist promoter has been shown to result in promoter-associated chromatin changes, allowing aberrant initiation of Xist transcription (9,10,40). In addition, forced Tsix expression during development results in Xist promoter methylation (41). Xist promoter methylation is also required to stably repress Xist at later stages of development in the absence of ongoing Tsix transcription, which is shut down in differentiated cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…He showed that Tsix can repress Xist and that this subsequently induces the expression of an X-linked GFP transgene in all extra-embryonic lineages of early postimplantation embryos, as well as in the parietal endoderm during development, but not in late-stage trophoblast giant cells or spongiotrophoblast cells (Ohhata et al, 2011). This indicates that the maintenance of imprinted XCI in some extra-embryonic lineages is highly dependent on Xist RNA.…”
Section: Meeting Reviewmentioning
confidence: 97%
“…That the loss of Xist IVS RNA in differentiating TS cells appears to facilitate reactivation of the hitherto inactive X seems to run counter to the idea that Xist is not required to maintain X-inactivation in differentiated cells. A recent study, however, demonstrates that maintenance of X-inactivation is Xist-RNA-dependent in some differentiated cell types [61]. Ohhata et al [61] showed that induced expression of Tsix by doxycycline could counteract Xist and shut it off in the visceral endoderm, leading to reactivation of the X-linked GFP transgene that had been repressed on the inactive X chromosome.…”
Section: Rstbroyalsocietypublishingorg Phil Trans R Soc B 368: 2011mentioning
confidence: 99%
“…A recent study, however, demonstrates that maintenance of X-inactivation is Xist-RNA-dependent in some differentiated cell types [61]. Ohhata et al [61] showed that induced expression of Tsix by doxycycline could counteract Xist and shut it off in the visceral endoderm, leading to reactivation of the X-linked GFP transgene that had been repressed on the inactive X chromosome. This effect was not seen in the trophoblastic lineages.…”
Section: Rstbroyalsocietypublishingorg Phil Trans R Soc B 368: 2011mentioning
confidence: 99%